Doris Lessing - Watkins, Susan, 1967- (Contemporary world writers, 2010)
In this book, Susan Watkins examines the writing career of the respected and prolific novelist Doris Lessing, who was awarded the Nobel Prize for Literature in 2007 and has recently published what she has announced will be her final novel.